An Interdisciplinary approach to urban design education: knowledge enhancement - Abu Saada, Hisham Galal (Journal of engineering sciences and information technology, 2018)
In this debate, we claim that scholars should consider multidisciplinary approach as a new concept for knowledge enhancement so that it can be applied in the process of urban design education. This research assumes that there is no clear conception of enlightenment in the preparation and teaching of educational programs in many fields of architecture, particularly in the urban design discipline and some Egyptian universities, which makes some of the students’ projects lose their relative quality. This research endeavors to emphasize the importance of accepting the multi-disciplinary approach related to knowledge-based urban design. The concluded section proposes the presentation of a specific declaration or document (Egyptian Manifesto). This document provides remarkable methodological guidelines, which is used to develop how researchers, scholars, and specialists think, and to raise the intellectual capability of practitioners. This research recommends that professionals begin to promote the efforts that develop knowledge.